KnowledgeBoat Logo

Mathematics

Solve for x : 5x+(x21)5x(x21)=75\dfrac{5x + (x^2 - 1)}{5x - (x^2 - 1)} = \dfrac{7}{5}.

Ratio Proportion

2 Likes

Answer

Given,

5x+(x21)5x(x21)=75\dfrac{5x + (x^2 - 1)}{5x - (x^2 - 1)} = \dfrac{7}{5}

Applying componendo and dividendo, we get :

5x+(x21)+5x(x21)5x+(x21)[5x(x21)]=7+57510x5x5x+(x21)+(x21)=12210x2(x21)=65xx21=65x=6(x21)5x=6x266x25x6=06x29x+4x6=03x(2x3)+2(2x3)=0(3x+2)(2x3)=03x+2=0 or 2x3=03x=2 or 2x=3x=23 or x=32.\Rightarrow \dfrac{5x + (x^2 - 1) + 5x - (x^2 - 1)}{5x + (x^2 - 1) - [5x - (x^2 - 1)]} = \dfrac{7 + 5}{7 - 5} \\[1em] \Rightarrow \dfrac{10x}{5x - 5x + (x^2 - 1) + (x^2 - 1)} = \dfrac{12}{2} \\[1em] \Rightarrow \dfrac{10x}{2(x^2 - 1)} = 6 \\[1em] \Rightarrow \dfrac{5x}{x^2 - 1} = 6 \\[1em] \Rightarrow 5x = 6(x^2 - 1) \\[1em] \Rightarrow 5x = 6x^2 - 6 \\[1em] \Rightarrow 6x^2 - 5x - 6 = 0 \\[1em] \Rightarrow 6x^2 - 9x + 4x - 6 = 0 \\[1em] \Rightarrow 3x(2x - 3) + 2(2x - 3) = 0 \\[1em] \Rightarrow (3x + 2)(2x - 3) = 0 \\[1em] \Rightarrow 3x + 2 = 0 \text{ or } 2x - 3 = 0 \\[1em] \Rightarrow 3x = -2 \text{ or } 2x = 3 \\[1em] \Rightarrow x = -\dfrac{2}{3} \text{ or } x = \dfrac{3}{2}.

Hence, x = 23 or 32-\dfrac{2}{3} \text{ or } \dfrac{3}{2}.

Answered By

3 Likes


Related Questions